Respiratory Support during Bronchiolitis Due to One Virus versus More Than One Virus: An Observational Study - Coleman, Thomas; Taylor, Alison; Crothall, Helen; Martinez, F. Eduardo (Journal of Pediatric Intensive Care, 2019)
Bronchiolitis is common during infancy and frequently leads to pediatric intensive care unit (PICU) admission. This study aimed to determine if there is a difference in the duration of respiratory support when bronchiolitis is due to one virus or more than one virus. This is a retrospective, observational study of cases admitted to PICU with confirmed bronchiolitis. There were 306 cases analyzed, 70% (215/306) were infected by a single virus and 30% (91/306) were infected with more than one virus. Both groups had similar duration of respiratory support and PICU length of stay (LOS). Hospital LOS was longer for the group with more than one virus.
Keywords: infant; bronchiolitis; viruses; critical care